(untitled) (Research, Society and Development, 2020)
The standardization process of certain technologies in the Brazilian Unified Health System must be proceded by cost-effectiveness analyzes. The catheterization procedure is performed in 8% of hospitalized patients and in 15% it causes complications. In view of this scenario, a technology that can provide safety for patients and professionals and reduce the rate of complications must be analyzed and perhaps incorporated into the medical routine. In this way, the objective is to determine the economic feasibility of the technique of central catheterization in a subclavian vein guided by ultrasound compared to guidance by anatomical references, from the perspective of the Brazilian Unified Health System. Through cost-effectiveness analysis using a decision tree model under a population of adult patients in a tertiary health care setting with materials and procedures costs estimated in Brazilian purchase records banks. The outcomes were defined in a literature review by incidence. The results showed that the intervention cost the procedure R53.81. Despite this, 80.1% of the simulations proved to be cost-effective and 16.5% “dominant”. Other factores corroborated the discussion, concluding the intervention as very cost-effective and the result brings security to de manager when making decisions regarding the standardization of technology.